TRADISI BAANTARAN JUJURAN DALAM PROSESI PERKAWINAN MASYARAKAT ADAT BANJAR PERSPEKTIF HUKUM ISLAM DAN TEORI KONSTRUKSI SOSIAL - Fadillah, Nor (Program Studi PAI STAI Al Falah Banjarbaru, 2022)
ABSTRACT: Tradition is an ancestral heritage that is believed by the community to be full of value. Likewise, in Banjar traditional marriages consisting of various traditions, including maantar honesty, namely the man is required to give some money and goods to the woman, but it is not uncommon because of this tradition someone fails to marry because he is unable to fulfill the woman's request. This study aims to examine more deeply the maantar honesty tradition in Keramat Village, using social construction theory, with a focus: (1) what is the background of the community carrying out the maantar honesty tradition (2) what are the goals of the community when carrying out the maantar honesty tradition. This type of research is juridical-empirical, with a sociological approach. The results of this study are twofold, First, the background of people using this tradition is due to the understanding of verses and hadiths of dowry, if the whole honesty is stated when the consent is granted, then it is included as dowry, if it is mentioned in part, then the rest is included as a gift. On the other hand, due to historical facts, variations in dowry have existed since the time of the Prophet Muhammad, in addition to the value contained in this tradition, so that this tradition becomes a law strengthened by the rule of